Usucapião judicial e a função social da propriedade territorial urbana: análise de processos de usucapião na comarca de Foz do Iguaçu - PR, entre os anos de 2015 a 2019 - Souza, Mauro Cesar João de Cruz e (2022)
With the Federal Constitution of 1988, private property became, definitively, conditioned to the fulfillment of its social function. Aligned with the Federal Constitution, the City Statute - Law 10.257/2001, outlined the guidelines of urban policy and defined the condition in which urban territorial property fulfills its social function, likewise Constitutional Amendment no 26/2000 inserted the right to housing among the social rights. The present work deals with the measurement of the social function of urban territorial property through adverse possession actions in the District of Foz do Iguaçu - PR, with analysis of adverse possession processes filed in this District, between the years 2015 to 2019. Will be seem the treatment of the republican constitutions of Brazil on private property since the Federal Constitution of 1891 to the Federal Constitution of 1988, as well as the asymmetry/symmetry of infraconstitutional legislation with the constitutional text. We will see the use of adverse possession as a mechanism to seek and the social function of property, explaining the various forms of adverse possession provided for in Brazilian legislation and more specifically on the extraordinary adverse possession because this is the most used form in Foz do Iguaçu in the survey period. It will be observed in the adverse possession actions proposed in the District of Foz do Iguaçu between the years 2015 and 2019, analyzing the fulfillment of the social function of ownership of the properties subject to adverse possession, the socioeconomic profile of the parties involved in the processes, the origin of possession, time average length of proceedings, forms of adverse possession used and land regularization through these actions. At the end, a parallel will be drawn between adverse possession, sometimes serving as an instrument for real estate regularization of properties that fulfill their social function, or serving as a means of disputing properties that do not fulfill their social function and are objects of real estate speculation.